2001
DOI: 10.1124/mol.60.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin Receptor EP4 Mediates the Bone Anabolic Effects of PGE2

Abstract: Prostaglandin (PG) E(2) is a potent inducer of cortical and trabecular bone formation in humans and animals. Although the bone anabolic action of PGE(2) is well documented, the cellular and molecular mechanisms that mediate this effect remain unclear. This study was undertaken to examine the effect of pharmacological inactivation of the prostanoid receptor EP(4), one of the PGE(2) receptors, on PGE(2)-induced bone formation in vivo. We first determined the ability of EP(4)A, an EP(4)-selective ligand, to act a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
127
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(137 citation statements)
references
References 28 publications
(43 reference statements)
7
127
1
2
Order By: Relevance
“…The role of this receptor in bone formation was suggested previously only indirectly by the use of a limited repertory of EP-acting compounds (18). We have found that activation of EP4 induced callus formation on the femur of mice and restored the volume of cancellous bone in OVX or immobilized rats.…”
Section: Discussionmentioning
confidence: 50%
“…The role of this receptor in bone formation was suggested previously only indirectly by the use of a limited repertory of EP-acting compounds (18). We have found that activation of EP4 induced callus formation on the femur of mice and restored the volume of cancellous bone in OVX or immobilized rats.…”
Section: Discussionmentioning
confidence: 50%
“…Although recent studies suggest a role for the EP2 receptor in PGE 2 -induced cellular response, a caveat with these studies is the use of cell culture systems in which the EP2 receptor is ectopically expressed [40]. Our studies, which are in agreement with several other reports [36], indicate an important role for the EP4 receptor for the following reasons: 1) PGE1-OH (relatively selective EP4 agonist), but not 17-phenyltrinor PGE 2 (EP1/EP3 agonist) induced ERK phosphorylation; 2) pretreatment of HCA-7 cells with AH6809 (EP1/EP2 antagonist) did not have any effect on PGE 2 -induced ERK phosphorylation; 3) L-161,982 at concentrations that does not bind to either EP1 or EP2 receptors [18] abrogated PGE 2 -induced ERK phosphorylation. Nevertheless, the relative contribution of the EP2 and EP4 receptors to human colon cancer will require further study.…”
Section: Discussionmentioning
confidence: 99%
“…U0126 and H-89 were purchased from Cell signaling technology (Beverly, MA) and Calbiochem (La Jolla, CA), respectively. A selective EP4 receptor antagonist L-161,982 [18] was from Merck-Frosst laboratories (Merck-Frosst, Canada). Antibodies against phospho-ERK (Tyr 304), and Egr-1 (sc-110) were from Santa Cruz Biotechnology Inc. (Santa Cruz, CA).…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
“…Recent studies using animals with deletion of either the EP2 or EP4 receptors or using selective agonists for these receptors have suggested that both EP2 and EP4 can mediate anabolic responses to PGE 2 (4)(5)(6)(7)(8)(9)(10), although the EP1 receptor may also be involved (11). Activation of EP2 and EP4 receptors increases cAMP and can also induce COX-2, which can result in auto-amplification of PGE 2 signaling (12).…”
Section: Introductionmentioning
confidence: 99%